2016
DOI: 10.1039/c5ay02379c
|View full text |Cite
|
Sign up to set email alerts
|

Label-free simple fluorescence assay of DNA polymerase using the G-quadruplex structure

Abstract: In this study, the G-quadruplex structure was used to detect the enzymatic activity and inhibition of the Klenow fragment exo−(KF−) in the presence ofN-methylmesoporphyrin IX (NMM) which binds specifically to the G-quadruplex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The corresponding IC 50 (the half‐maximal inhibition of KF‐) value was 6.23 μM, which was determined from the nonlinear regression analysis of the data in Figure 4. The results indicated that 5‐fluorouracil inhibited DNA polymerase activity effectively like the drugs of daidzein and chloroquine 15,16 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The corresponding IC 50 (the half‐maximal inhibition of KF‐) value was 6.23 μM, which was determined from the nonlinear regression analysis of the data in Figure 4. The results indicated that 5‐fluorouracil inhibited DNA polymerase activity effectively like the drugs of daidzein and chloroquine 15,16 …”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that 5-fluorouracil inhibited DNA polymerase activity effectively like the drugs of daidzein and chloroquine. 15,16…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations